Conflicts of interest in scientific publishing - Amigo, Ignacio (EMBO Rep, 2017)
Gold OA as a publishing model has created conflicts of interest for authors and journals that create a risk for research integrity. Alternative models of publishing and peer review could resolve some of these conflicts. [Image: see text]